"What seems to be the problem?" A myriad of terms for mental health and behavioral concerns - O'Reilly, Michelle (Disability Studies Quarterly, 2009)
The fundamental philosophy of family therapy is to "treat" the family as a unit. It sets out to provide assistance to families with troubles in a way to make them work together in a more functional way. Parents of children with difficulties however, do not necessarily consider the underlying principles of the discipline and seem less concerned with institutional practices. It is salient in family therapy for parents (of disabled children) to locate their child(ren) as the central problem and as the reason for their acquisition of therapy. Using family therapy data, I demonstrate how they construct their "problem child" in interrelated ways, in a way that deviates accountability from them as parents but more importantly works as a display of misunderstandings of mental health issues and concepts. This has wider implications for therapeutic practice and agency responsibility, and further implications for a need for consistent terminology and education for parents.